2022
DOI: 10.1108/febe-12-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 outbreaks on the lower-income groups and attainments of SDGs: a study of the fast-growing commercial capital city, Chittagong, Bangladesh

Abstract: PurposeThe emergence of COVID-19 and its spread led to severe social, economic and livelihood impacts around the world. This study documented the socioeconomic impacts of COVID-19 outbreaks and lockdown on the lower-income groups. Also illustrated the impacts on the attainment of SDGs in the context of the slums of Chittagong City.Design/methodology/approachBoth qualitative and quantitative data have been collected from the 150 respondents through questionnaire surveys in the slums.FindingsThe lockdown led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Therefore, the findings of this study did not offer clear support for Hypothesis 7, which stated that there might not be any significant difference among households across the living divisions in adapting mechanisms to maintain their quality of life during the pandemic. This result is consistent with previous studies, which stated that households in different regions included different levels of coping strategies [90,91]. One of the potential explanations for this finding is that they were less likely to implement expenditure-minimizing mechanisms (See Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the findings of this study did not offer clear support for Hypothesis 7, which stated that there might not be any significant difference among households across the living divisions in adapting mechanisms to maintain their quality of life during the pandemic. This result is consistent with previous studies, which stated that households in different regions included different levels of coping strategies [90,91]. One of the potential explanations for this finding is that they were less likely to implement expenditure-minimizing mechanisms (See Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…These sectors are closely associated with the Garment Industry and Export Processing Zones (EPZs). Prolonged lockdowns and restrictions on various activities destroyed the income sources of these households and at the same time led to inflation, which jeopardized their purchasing power [90,91]. Moreover, after the closure of the garment factory, those who had worked there before were not compensated, and those who depended on small businesses could no longer do so [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…were the key issues faced by slum dwellers. Similarly, in their study, Fattah et al (2022) found that the financial crisis of slum dwellers significantly increased stress and affected their livelihood. Rising unemployment and limited income also triggered many families to be unable to pay their house, water, and rent bills at the end of the month, which led to the risk of becoming homeless.…”
Section: Slum Dwellers Faced Different Types Of Challenges For Their ...mentioning
confidence: 83%
“…A survey on the effect of COVID-19 on a range of income, classified as upper income, middle income, and lower income, shows that those adults receiving minor payments have suffered the most wage cuts (Parker et al, 2020). One effect of the COVID-19 lockdowns was the decrease of the income level by 90%, which affected 97.33% of the respondent's livelihood, resulting in to decrease in their income level (Fattah et al, 2022). Another article says that the Hospitality industry, a low-earning salary group, is suggested to have a disproportion effect caused by the COVID-19 Pandemic (Aharon et al, 2021).…”
Section: Covid-19 Effect On Salary-range Groupmentioning
confidence: 99%